2013
DOI: 10.1128/aac.00220-13
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus Thiol/Oxidative Stress Global Regulator Spx Controls trfA , a Gene Implicated in Cell Wall Antibiotic Resistance

Abstract: S. aureus combats cell wall antibiotic stress by altered gene expression mediated by various environmental signal sensors. In this study, we examined the transcriptional regulation of trfA, a gene related to mecA of Bacillus subtilis encoding an adaptor protein implicated in multiple roles, notably, proteolysis and genetic competence. Despite strong sequence similarity to B. subtilis mecA, the function of S. aureus trfA remains largely unexplored; however, its deletion leads to almost complete loss of resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 74 publications
3
46
0
Order By: Relevance
“…trfA is transcribed from three promoters, generating transcripts of closely related sizes of 751, 818, and 898 bases, which can be seen as a single transcript in a 0.7% agarose gel (28). The changes to trfA transcription during various growth phases remain unclear, however.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…trfA is transcribed from three promoters, generating transcripts of closely related sizes of 751, 818, and 898 bases, which can be seen as a single transcript in a 0.7% agarose gel (28). The changes to trfA transcription during various growth phases remain unclear, however.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of spx transcription by RT-PCR have shown that the gene product of spx likely activates one or more of these transcripts of trfA (28). Spx is a thiol-sensitive transcriptional regulator that is itself proteolytically regulated and is responsible for controlling the adaptation and survival of S. aureus in environments with oxidative stress.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Spx controls gene expression by interacting directly with the ␣ subunit of the RNA polymerase (45). The Spx-controlled trfA gene was recently shown to be required for the ability of subinhibitory concentrations of ␤-lactam antibiotics to induce the hVISA phenotype, raising the intriguing possibility that the elevated Spx level may contribute to the decreased susceptibility to daptomycin, vancomycin, and ␤-lactams (46,47). Unfortunately, attempts to examine this hypothesis by introducing an spx mutation into single mutants were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%